Assessing the Role of Government Policies in Supporting Sustainable Business Practices Among Local Enterprises - Sinambela, Tohap; Mustari, Vera Herlina; B.W, Yose Cahyo (Institut Penelitian dan Pengembangan Mandalika Indonesia, 2026)
This study assesses the role of government policies in supporting sustainable business practices among local enterprises. Using a library research methodology, the study analyzes secondary data from academic journals, government reports, industry publications, and case studies to examine how government interventions—such as financial incentives and regulatory measures—impact local businesses’ ability to adopt sustainability initiatives. The findings reveal that while these policies have proven effective in promoting sustainable practices, challenges remain in terms of accessibility and awareness. The study emphasizes the need for simplified application processes and more tailored policy support to further enhance the adoption of sustainability in local enterprises. The research provides valuable insights for policymakers aiming to create more effective frameworks to support sustainable business practices at the grassroots level.